POTENTIAL OF ENVIRONMENTAL TRANSBOUNDARY HARM CAUSED BY GENETIC MODIFIED ORGANISM AS MECHANISM FOR BIOREMEDIATION: A CASE STUDY IN CORAL TRIANGLE BIODIVERSITY HOTSPOT - Rahmadhitya M Putra (International Law Department, Faculty of Law Universitas Padjadjaran, 2022)
Biotechnology was introduced to the world of industries in the early 2000s. Its profound impact has continued shaping the mechanism of environmental clean-up. The development of biotechnology has received a wide variety of attention. Hence, bioremediation becomes integral to the notion of sustainability for environment quality. Especially, within oil & gas sector the damage can be substantial towards the environment longevity. Specifically, one of the most monumental in terms of potential harm is offshore oil & gas operations. On the other hand, the sophistication within oil & gas sector has become a rapid development over the last few years. It’s based on fact the oil & gas ought to be drilled deeper within the ocean floor. As the depth of drilling increase, so does the complexity of the oil composition. With this, regular bioremediation mechanism might not be able to handle the structural chemical complexity. Thus, a genetic modification appeared as the most efficient effort to reduce environmental damage and strike out the oil chemical complexity. However, it’s easier said than done. This because ethically, the modification potentially could harm the natural environment. Not just nationally but also transboundary. Therefore, the issue also discusses a new area of multidisciplinary approach where expected law meets an unprecedented amount of scientific efficiency.